A study on the effectiveness of the virtual recruitment process of new hires during the pandemic situation - Hoque, Fatema Sanzida (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.